2020
DOI: 10.36660/abc.20190731
|View full text |Cite
|
Sign up to set email alerts
|

Posicionamento Luso-Brasileiro de Emergências Hipertensivas – 2020

Abstract: Nota: estes Posicionamentos se prestam a informar e não a substituir o julgamento clínico do médico que, em última análise, deve determinar o tratamento apropriado para seus pacientes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 110 publications
0
5
0
2
Order By: Relevance
“…The frequency of hypertensive crises increases from the fifth decade of life onward, due to a linear increase in blood pressure levels, age progression, and less chance of BP control. 2,19 The low adherence to drug treatment found, associated with uncontrolled BP, is a behavior also evidenced by other studies with adult hypertensive patients being treated for HBP. 8,9,16,21 Another study showed that good adherence to drug treatment was associated with better BP control in hypertensive patients.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The frequency of hypertensive crises increases from the fifth decade of life onward, due to a linear increase in blood pressure levels, age progression, and less chance of BP control. 2,19 The low adherence to drug treatment found, associated with uncontrolled BP, is a behavior also evidenced by other studies with adult hypertensive patients being treated for HBP. 8,9,16,21 Another study showed that good adherence to drug treatment was associated with better BP control in hypertensive patients.…”
Section: Discussionmentioning
confidence: 62%
“…The occurrence of emergency room care for HBP in the last 6 months was associated with lack of BP control; however, we did not find studies that evaluated this association, although several evidence points to the frequent search for emergency care for BP elevations 32 . High BP levels may be related to the frequency of times an individual goes to the emergency room, due to the presence of symptoms and/or complications, among the most common: headache, vertigo, pain in the precordial region, nausea, vomiting and others, with main focus on the neurological, cardiovascular, and renal systems 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nos países de maior desenvolvimento, as taxas de controle pressórico são maiores (28,4%) do que as de países com menor grau de desenvolvimento (7,7%). (2) Na realidade brasileira, estudo realizado em 2015 revela que a taxa de controle varia de 10,4% a 35,2% a depender da região do país. (3) Marques et al, em sua revisão sistemática realizada em 2018 (4) , destacaram os fatores associados à hipertensão arterial sistêmica: Idade e IMC elevados constam como as variáveis mais prevalentes.…”
Section: Introductionunclassified